The Intersection Between Mining Contaminants and Hunting in Northeastern Ontario Communities - Andrews, Carly (Université d'Ottawa / University of Ottawa, 2018)
There is a plethora of research circulating in the academic word related to Indigenous hunters and how industrial development is affecting their traditional lifestyles; of particular concern are the toxic exposures derived from these industrial activities as well as the effects these are having on animal and human health. However, relatively little research exists on the ways in which non-Indigenous hunters are being impacted by and perceive the environmental risks posed by industrial activities (i.e., mining contaminants). The purpose of this study was two-fold: to investigate whether there is a relationship between hunting practices of non-Indigenous hunters and their health status and personal wellbeing as well as examining how the perception of environmental risk associated with mining contaminants might affect the hunting practices, health and wellbeing of non-Indigenous hunters living in northeastern Ontario communities. The study involved survey questionnaires that were distributed in four northeastern Ontario communities (Onaping Falls, Porcupine, Wawa, and Hearst) where a total of 390 hunters, non-hunters, and former hunters voluntarily participated. Findings from this study indicated a few relationships between hunting practice variables (discarding/giving away animals and hunting near mine or tailings sites) and general health, physical health, and physical health readiness variables but no relationships with personal wellbeing. Furthermore, significant associations were found between two hunting practice variables (hunting near mine tailings and discarding/giving away hunted animals) and the two risk perception variables. In addition, worrying about mining contaminants was significantly associated with reduced levels of mental health and personal wellbeing. Despite the significant associations, few hunters took actions as a result of their concern or worry over mining contaminants although it must be noted that only a minority of hunters always or very frequently hunted near mine or tailings sites. Either hunters did not perceive the risks as being high or they merely have a high risk tolerance. Further research is required to delve deeper into the issues explored in this research study.
Keywords: Mining; Contaminants; Hunting; Health; Well being; Physical Health; Mental Health; Northeastern Ontario